Patterns of amino acid intake are strongly associated with cardiovascular mortality, independently of the sources of protein. (27th September 2019) - Tharrey, Marion; Mariotti, Francois; Mashchak, Andrew; Barbillon, Pierre; Delattre, Maud; Huneau, Jean-François; Fraser, Gary E
Abstract: Background: The intake of specific amino acids (AA) has been associated with cardiovascular health, but amino acids are consumed together as dietary protein. Here we investigated the association between identified patterns of amino acid intake and cardiovascular mortality. Methods: A total of 2216 cardiovascular deaths among 79 838 men and women from the Adventist Health Study-2 were included in our analysis. Baseline dietary patterns based on the participants' amino acids intakes were derived by factor analysis. Using Cox regression analyses, we estimated multivariate-adjusted hazard ratios (HRs) adjusted for sociodemographic and lifestyle factors and other dietary components. Results: Three patterns of amino acids were identified. Factor 1 was positively associated with cardiovascular disease (CVD) mortality [hazard ratio (HR)Q5-Q1 : 1.62, 98.75% confidence interval (CI): 1.15, 2.28; P -trend <0.001]; and Factors 2 and 3 were inversely associated with CVD mortality (HR Q5-Q1 Factor 2: 0.74, 98.75% CI: 0.53, 1.04; P -trend <0.01 and HR Q5-Q1 Factor 3: 0.65, 98.75% CI: 0.44, 0.95; P -trend <0.05]. The associations with Factor 1 (with high loadings on indispensable amino acids such as branched chain amino acids, lysine, methionine) and Factor 3 (with high loadings on non-indispensable amino acids, namely arginine, glycine, aspartate+asparagine) remained significant after further adjustment for nutrient intake and for the five protein source patterns identified previously (HR Q5-Q1 : 1.56 (0.99, 2.45) and 0.55 (0.35, 0.85); P -trends < 0.01). Conclusions: Indispensable AA have a positive and some non-indispensable AA have a negative, independent, strong association with the risk of cardiovascular mortality.